Metabolism of triglyceride-rich lipoproteins during alimentary lipemia. - Karpe, F; Steiner, G; Olivecrona, T; Carlson, L; Hamsten, A (1993)
The metabolism of chylomicron remnants and VLDL was studied in healthy controls and normo- (NTG) and hypertriglyceridemic (HTG) patients with coronary artery disease after intake of an oral fat load. Specific determination of apo B-48 and B-100 enabled separation of the respective contribution of the two lipoprotein species. The postprandial plasma levels of small (Sf 20-60) and large (Sf 60-400) chylomicron remnants increased in controls and NTG patients. In contrast, only large chylomicron remnants increased in the HTG patients. An increase of large VLDL was seen in response to the oral fat load in all groups, whereas small VLDL were either unchanged in the controls and the NTG patients, or decreased in the HTG patient group. The whole plasma concentration of C apolipoproteins was essentially uninfluenced by the oral fat load, whereas the content in large triglyceride-rich lipoproteins paralleled the apo B elevations in controls and NTG patients. An even more prominent increase of apo B in large triglyceride-rich lipoproteins in the HTG group was not accompanied by an increase of C apolipoproteins. These findings indicate that chylomicrons compete with VLDL for removal of triglycerides by lipoprotein lipase and that the postprandial metabolism of triglyceride-rich lipoproteins is severely defective in hypertriglyceridemia.